Influence of Achieved Status on Clean and Healthy Behavior in Coastal Sasak West Pasaman - Prarikeslan, Widya; Mariya, Sri (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This research is a survey research with explanatory research, data related to the achieved status and behavior of clean and healthy living is taken directly in the field. The method used in this research is correlational method, which consists of two variables are variable X (status achieved) and variable Y PHBS. Data analysis technique used multiple linear regression test at 95% confidence level. Data processing using SPSS to know the relationship between the status achieved with the clean and healthy behavior. Tool of data collection used in this research is a questionnaire. Implementation of this activity is planned for 1 phase done in 2016 with analyze, the relationship between the status achieved with the clean and healthy behavior.